2015
DOI: 10.1371/journal.pone.0136739
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Plasma C-Terminal Endothelin-1 Precursor Fragment Concentrations Are Associated with Less Anxiety in Patients with Cardiovascular Risk Factors. Results from the Observational DIAST-CHF Study

Abstract: BackgroundThe role of endothelin-1 (ET-1) in the neurobiology of anxiety is unknown, therefore, we assessed in the observational multicenter DIAST-CHF study whether the C-terminal ET-1 precursor fragment (CT-proET-1) is linked to anxiety.MethodsPlasma concentrations of CT-proET-1 were measured in a total of 1,410 patients presenting with cardiovascular risk factors (mean age 66.91±8.2 years, 49.3% males, mean left ventricular ejection fraction 60.0±8.2%) who had completed the Hospital Anxiety and Depression Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…With regard to depression, the results of the present study were in line with the literature, 1,17,30,35,36 since the profile of these patients was predominantly female, surviving on the minimum wage or less, and married or in a stable relationship. This was also the case with the patients with anxiety, contradicting both the study that found a higher prevalence in women with no sexual partner, since divorced women were at higher risk of suicide because of depression than those who were married or widowed, 14 and also one that found a discrete prevalence among males and another that found equal frequency in both sexes.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…With regard to depression, the results of the present study were in line with the literature, 1,17,30,35,36 since the profile of these patients was predominantly female, surviving on the minimum wage or less, and married or in a stable relationship. This was also the case with the patients with anxiety, contradicting both the study that found a higher prevalence in women with no sexual partner, since divorced women were at higher risk of suicide because of depression than those who were married or widowed, 14 and also one that found a discrete prevalence among males and another that found equal frequency in both sexes.…”
Section: Discussionsupporting
confidence: 90%
“…1,9,15,[17][18][19]35,36 Another point that it is indispensable to discuss is that both anxiety and depression are risk factors for CVD, such as AMI, stroke, and PAD. 1,15,17,30,[34][35][36][37][38] This could be because patients with anxiety/depression tend to have a less healthy lifestyle, with dietary errors and without physical exercise, 33,39 as was observed in our sample, the great majority of whom did not do regular physical exercise. However, in contrast to some other studies, 33,36 this factor did not affect the presence of depression.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Beside its prognostic value for heart failure patients [ 20 , 49 , 50 ], our data from the Diast-CHF study suggest an unknown mechanism of galectin-3 in the regulation of anxiety also in humans. Thus, this galactoside-binding lectin may be added to the growing list of peptides functioning as prognostic biomarkers of heart failure (NT-proBNP, NT-proANP, MR-proANP, CT-ET-1, CT-proAVP, and MR-pro-adrenomedullin) that, in addition, negatively associate with anxiety [ 13 16 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelin-1 (ET1) is a 21-amino-acid peptide and a potent vasoconstrictor that was first isolated from the supernatant of cultured porcine aortic endothelial cells 15 . Although many previous human studies have shown links between ET1 and diseases such as arterial hypertension and renal disease 16 19 , recent patient data has shown possible connections between ET1 and anxiety 20 , 21 and between ET1 and depression 22 . ET1 is widely distributed in the CNS and acts on two distinct G protein-coupled receptors: the ETA receptor (ETAR) and the ETB receptor (ETBR) subtypes 16 , 23 – 25 .…”
Section: Introductionmentioning
confidence: 99%